Genetic variability amongst Fusarium spp. in the section Liseola from bakanae-infected rice in Malaysia and Indonesia by RAPD analysis. - Mohd Zainuddin, Nur Ain Izzati; Salleh, Baharuddin (Malaysian Society of Applied Biology, 2009)
RAPD was used to assess genetic relatedness amongst 59 strains of Fusarium spp. in the section Liseola obtained from rice plants showing bakanae symptoms from different major granary areas in Malaysia and Indonesia, as well as 14 strains of standard testers from U.S.A. RAPD analysis using 10 nucleotides with 60 – 70% G+C contents primers i.e. OPA-02 (5’-tgc-cga-gct-g-3’), OPA-04 (5’-aat-cgg-gct-g-3), OPA-09 (5’-ggg-taa-cgc-c-3’), OPA-17 (5’-gac-cgc-ttg-t-3’), OPT-11 (5’-ttc-ccc-gcg-a-3’), OPT-18 (5’-gat-gcc-aga-c-3’), OPU-06 (5’-acc-ttt-gcg-g-3’), OPU-16 (5’-cgt-cgc-tgg-a-3’), OPV-06 (5’-acg-ccc-agg-t-3’) and OPV-16 (5’-aca-ccc-cac-a-3’) showed variations on DNA profiles between the species, indicating the species were genetically heterogeneous. Dendograms from cluster analysis based on UPGMA showed that the six species of Fusariumwere clustered separately.